Message from the Editor-in-Chief - D. Skaper, Stephen (CNS & Neurological Disorders - Drug Targets, 2012)
In 2012 CNS & Neurological Disorders - Drug Targets will enter its 11th year of publication. This year will also mark my third year as Editor-in-Chief. Since taking the helm of the journal a number of changes have been introduced, one of my first having been to renew and expand our Editorial Advisory Board to include a broader base of expertise in this incredibly fast-moving area of science. Starting last year, and continuing in 2012 CNS & Neurological Disorders - Drug Targets expands its production calendar to 8 issues per year, up from the previous frequency of 6 issues. Other developments, which I believe will strengthen interest in the journal and encourage an increasingly diverse range of topic submissions is the inclusion, apart from reviews, of both full-length and letter-type research articles as well as clinical case reports. We have added also sections dealing with short Research Highlights discussing recent, high impact publications of relevance to the journal's mission together with reports on meetings. A number of cutting-edge Hot Topic issues are in the works for 2012, including nanoneuroscience, endocannabinoids, novel strategies for neuropsychiatric disorders, and purinergic receptor signaling. CNS & Neurological Disorders - Drug Targets is always open to theme issue proposals from our readers, and I encourage you to submit your ideas for consideration. With best wishes for a productive New Year,